Flexible composite mechanical energy harvester from a ferroelectric organoamino phosphonium salt - Vijayakanth, Thangavel; Srivastava, Anant Kumar; Ram, Farsa; Kulkarni, Priyangi; Shanmuganathan, Kadhiravan; Praveenkumar, Balu; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2018)
A new binary organic salt diphenyl diisopropylamino phosphonium hexaflurophosphate (DPDPPF6) was shown to exhibit a good ferroelectric response and employed for mechanical energy harvesting application. The phosphonium salt crystallizes in the monoclinic noncentrosymmetric space group Cc and exhibits an H-bonded 1D chain structure due to N-HF interactions. Ferroelectric measurements on the single crystals of DPDPPF6 gave a well-saturated rectangular hysteresis loop with a remnant (P-r) polarization value of 6Ccm(-2). Further, composite devices based on polydimethylsiloxane (PDMS) films for various weight percentages (3, 5, 7, 10 and 20wt%) of DPDPPF6 were prepared and examined for power generation by using an impact test setup. A maximum output peak-to-peak voltage (V-PP) of 8.5V and an output peak-to-peak current (I-PP) of 0.5A was obtained for the non-poled composite film with 10wt% of DPDPPF6. These results show the efficacy of organic ferroelectric substances as potential micropower generators.
Keywords: binary phosphonium salts; energy conversion; ferroelectricity; hydrogen bonding; polymer composites

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus